Conflicts and delays in mega construction projects – Kuwait International Airport Cargo City - Alazemi, Mohammad KhTh E; Mohiuddin, A. K. M. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Mega construction projects, in general, require a lot of planning in terms of land acquisition, estimating material cost, human resources, financials, safety, and many more. It is a common scenario with delays occurring in such mega-projects attributing to increased project costs, delays in work completion. It leads to creating a negative impact on the prospects of the effective utilization of the project output in terms of space, facility, and resources to commence work at that location. This study intended to identify the factors that could potentially contribute to project delays and possible methods of resolving the conflicts that have aroused. A case study on Kuwait International Airport Cargo City was conducted quantitatively as well as qualitatively. It is learned that management conflicts have a significant impact on creating project delays, due to poor management, lack of effective communication, and ineffective utilization of resources.